Transformative learning theory and praxis new perspectives and possibilities - Kostara, Effosyni; Gavrielatos, Andreas; Loads, Daphne (Routledge, 2022)
"Transformative Learning Theory and Praxis examines the multi-faceted nature of transformative learning and transformation theory including - its merits, restrictions and possibilities, and presents carefully chosen international case studies and theoretical approaches that enrich the application of the theory within a wide variety of educational settings. By including new approaches to transformative learning theory, this book provides examples and teaching approaches coming from a variety of disciplines, including higher education, arts, classics, new technologies and academic development. It bridges the gap between theory and practice to help teachers and adult educators embed potentially transformational techniques in the curriculum. Based on in-depth research, this key title provides a means of measuring and documenting transformative outcomes in qualitative studies of high impact learning experiences, and raises new questions and opportunities for the future development of the field. Transformative Learning Theory and Praxis is a must-read text for anyone interested in the research behind, and applications of, transformative learning and transformation theory, including researchers, students and policy-makers in the field"--
Keywords: Transformative learning; Apprentissage transformateur; Aufsatzsammlung